EXPERIMENT: IMPROVE THE FOREARM PASS SKILL OF VOLLEYBALL THROUGH PAIR TRAINING - Zainur Zainur (Journal Physical Education, Health and Recreation, 2019)
This research aimed to know the increase in the skills of forearm pass volleyball athletes through the exercises in pairs. The population was the athletes of volleyball MVC (Consensus Volly Club) Pekanbaru that amounted to as many as 12 people. The sample used the technique of total sampling so that the amount of sample was 12 people. The instrument in this study was a test of the skills of forearm pass volleyball. Analysis techniques used test t. Based on the data analysis and discussion, it could be concluded that the improvement of the skills of forearm pass volleyball athletes MVC (Consensus Volly Club) Pekanbaru through pairing exercises with proven results tcalculate 4,024> ttable 1,796 at α = 0.05.